2017
DOI: 10.1103/physrevb.95.134506
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity and unexpected chemistry of germanium hydrides under pressure

Abstract: Following the idea that hydrogen-rich compounds might be high-Tc superconductors at high pressures, and the very recent breakthrough in predicting and synthesizing hydrogen sulfide with record-high Tc = 203 K, ab initio evolutionary algorithm for crystal structure prediction was employed to find stable germanium hydrides. In addition to the earlier structure of germane with space group Ama2, we propose a new C2/m structure, which is energetically more favorable at pressures above 278 GPa (with inclusion of zer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
(67 reference statements)
0
6
0
Order By: Relevance
“…Because of high concentration of hydrogen in hydrogen-rich hydrides, zero-point energy (ZPE) might be important in determining the relative stability of hydrogen-rich phases; however, in our previous studies 22,40 , we showed that this quantum effect does not change the topology of the phase diagram, and quantitative effects are just moderate shifts in transition pressures. For example, for GeH 4 the inclusion of ZPE shifts the transition pressure Ama2 → C2/m from 300 to 278 GPa 40 . Among the stable phases predicted, we have synthesized , , and .…”
Section: Resultsmentioning
confidence: 73%
“…Because of high concentration of hydrogen in hydrogen-rich hydrides, zero-point energy (ZPE) might be important in determining the relative stability of hydrogen-rich phases; however, in our previous studies 22,40 , we showed that this quantum effect does not change the topology of the phase diagram, and quantitative effects are just moderate shifts in transition pressures. For example, for GeH 4 the inclusion of ZPE shifts the transition pressure Ama2 → C2/m from 300 to 278 GPa 40 . Among the stable phases predicted, we have synthesized , , and .…”
Section: Resultsmentioning
confidence: 73%
“…Pressures in the megabar (100 GPa) range can render some of these compounds metallic, through band overlap. Some of these metallic molecular hydrides, such as phosphorous, silicon or sulfur hydrides, exhibit superconductivity, with T c s that can be as high as 100 K [9,[26][27][28][29][30][31][32][33]. Increasing pressure even further, in a few systems molecular bonds break, and, as additional hydrogen is incorporated into the A-H lattice, compounds with completely different stoichiometries and geometrical motifs form, in which hydrogen and the guest atom arrange in highly symmetric structures, which are metallic and held together by covalent, directional bonds.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent exceptional interest was attracted to hydrides due to experimental and theoretical findings of high-TC superconductivity under high pressures. [12][13][14][15][16][17][18][19][20] Moreover, recent theoretical investigation of new hydrides in the Ge-H system 21 26 reported about relatively high possible transition temperature ~ 51 K at 130 GPa in FeH5. All these findings motivate us to study in details the Fe-H system, in particular, stability and superconducting properties of new phases.…”
Section: Introductionmentioning
confidence: 99%
“…3 Recent exceptional interest was attracted to hydrides due to experimental and theoretical findings of high-TC superconductivity under high pressures. [12][13][14][15][16][17][18][19][20] Moreover, recent theoretical investigation of new hydrides in the Ge-H system 21 (TC ~ 60 K), Sn-H 19 (TC ~ 100), MgGeH6 22 (TC ~ 132 K), H-S 14 (TC ~200 K) systems and in Th-H 23 and U-H 20 systems (TC ~ 194 K) at high pressures as well as landmark achievements in experimental synthesis of H3S 17 (TC ~ 203 K), PH3 24 (TC ~ 100 K), Si2H6 25 (TC ~ 76 K) inspire exploration of new hydrides. Fresh theoretical work made by Majumdar et al 26 reported about relatively high possible transition temperature ~ 51 K at 130 GPa in FeH5.…”
Section: Introductionmentioning
confidence: 99%